Protected Blend of Organic Acids and Essential Oils Improves Growth Performance, Nutrient Digestibility, and Intestinal Health of Broiler Chickens Undergoing an Intestinal Challenge - Stefanello, Catarina; Rosa, Daniele P.; Dalmoro, Yuri K.; Segatto, Ana L.; Vieira, Marcia S.; Moraes, Mariana L.; Santin, Elizabeth (Frontiers in Veterinary Science, 2020)
The growing restriction of antibiotic growth promoter (AGP) use in farming animals has raised a concern regarding the viability of the animal production system. In this new context, feed additives with proven positive impact on intestinal health may be used as strategy to avoid losses on performance. The aim of this study was to evaluate the effects of a protected blend of organic acids and essential oils [P(OA+EO)] on growth performance, nutrient digestibility and intestinal health of broiler chickens. A total of 1,080 Cobb × Cobb 500 male broilers were randomly distributed in 4 treatments with 10 replicates (27 birds/each). Treatments were as follow: non-challenged control; challenged control; AGP (enramycin at 10 g/t); and P(OA+EO) at 300 g/t. All birds on challenged groups were challenged with Eimeria spp. at 1 d and with Clostridium perfringens at 11, 12 and 13 d. Body weight gain (BWG), feed intake and feed conversion ratio (FCR) were evaluated until 42 d. At 17 d, one bird per pen was orally gavaged with fluorescein isothiocyanate-dextran (FITC-d) and blood samples were collected for FITC-d detection to assess intestinal permeability. At 21 d, apparent ileal nutrient and energy (IDE) digestibility, intestinal macroscopic and histologic alterations (ISI) and, expression of mucin2 (MUC2), claudin1 (CLDN1) and occludin (OCLN) genes in the jejunum were evaluated. From 1 to 42 d, birds from the non-challenged and P(OA+EO) groups had greater (P < 0.001) BWG compared to challenged control and AGP groups. The challenged control group presented the worst FCR (P < 0.001). IDE was 106 kcal/kg greater when broilers were fed P(OA+EO) compared to the challenged control group. Broilers supplemented with P(OA+EO) had improved intestinal integrity with lower blood FITC-d concentration and ISI scores, and greater expression of MUC2, CLDN1 and OCLN genes compared to the challenged control group (P < 0.05). In conclusion, the P(OA+EO) and the AGP led to increased growth performance, nutrient digestibility and intestinal health of challenged broilers. A marked difference occurred in favor of the P(OA+EO), suggesting that this blend may be used to improve intestinal health and broiler growth performance in AGP free programs.